Groundnut export tax in Senegal: Winners and losers - Fofana, Ismaël; Badiane, Ousmane; Camara, Alhassane; Goundan, Anatole (International Food Policy Research Institute, 2018)
Groundnuts are the most common cash crop and the main source of income for farmers in Senegal. Previously marginal, groundnut exports surged between 2011 and 2013. This new dynamic motivated the Government of Senegal to introduce a tax on groundnut exports in 2017. Senegal is a price-taker in the international groundnut market. Thus, the ex-ante simulation of the export tax on groundnuts results in a decreasing surplus for groundnut producers, while the surpluses of groundnut processors, the Government, and consumers increase. However, the positive effect on consumers is reversed if the introduction of the export tax is associated with a public investment-led groundnut productivity increase. The tax appears to be biased in favor of the export-oriented groundnut oil industry. Although the groundnut productivity increase mitigates the producers’ loss, it widens the benefit accruing to the groundnut processors. The induced increase of groundnut oil exports and the exchange rate effect exacerbate the producers’ loss. The associated negative income effect exceeds the positive price effect, leading to a decline in consumers’ surplus. Therefore, the introduction of an export tax does not necessarily increase consumers’ surplus in a country with weak market power. The economic structure and the external trade features of the country are as relevant as the fiscal policy decisions associated with the implementation of the trade reform.